Studi Evaluasi Formatif Pengelolaan Ekowisata ‘Burung Indonesia’ di Mbeliling, Flores - Agung Yoga Asmoro; Thamrin Biwana Bachri; Firdaus Yusrizal (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2021)
Covid pandemic is hitting global tourism, Indonesia is no exception. However, there is hope that tourism will improve in the future. Ecotourism is one product that is considered to be capable of being the solution. Burung Indonesia is the main ecotourism operator in Flores, its activities are located in the Mbeliling area about 50 km from Labuanbajo. Is the ecotourism management carried out well and in accordance with global sustainable tourism standards? This study aims to evaluate the management of ecotourism in Mbeliling, Flores by referring to the overall criteria and indicators required by GSTC v2.0 The method used in applied social research formative evaluation is descriptive qualitative. Data collection was carried out directly through comprehensive observation and in-depth interviews for five days in the field. Secondary data obtained through documentation, historical comparison, and supported by quantitative non-reactive data. In the next stage, the analysis of research is more emphasized on the analysis of literature conducted descriptively. The results of the study revealed unsatisfactory results for managers. The results of this evaluation should be used as a reference for future improvements, so that they become superior ecotourism operators and in accordance with sustainable tourism practices. Keyword: Ecotourism; Formative Evaluation Research; GSTC v2.0; Mbeliling; Sustainable Tourism